Analysis of Students’ Vocabulary in Learning English - Ivan Susanto Salawazo; Marintan Simbolon; Vivi Enjelia Hutabarat; Achida N Veronika; Erikson Saragih (Linguistic, English Education and Art (LEEA) Journal, 2020)
The purpose of this study was to analysis students’ vocabulary in learning English of Ninth grade at SMP Swasta Yayasan Pangeran Antasari, Medan in the academic year of 2018/2019. The researchers used descriptive qualitative method to describe and implementing factual condition and characteristic. There are 72 students that decided two classes at ninth grade as the population. But the researcher only took one class consists of 36 students as the sample. To collecting data, researchers use questionnaire and vocabulary comprehension test as procedure. In analyzing the data, the researchers identifying the difficulties of students’ vocabulary and cause difficulties by analyzing students answer sheets and their mistakes. There were 25 students (70%) incorrect answer in the questions. There were 6 students (16%) in modal, there were 8 students (23%) in simple past tense, There were 8 students ( 24 %) in simple present tense, 3 students (7%) troubled in simple continuous tense. Meaning. Students who gave incorrect answer in the questions were 29 students (82%). Others difficulties is translation being other types of the questions that examined in this research. it was found that there were 23 students (64%) who were unable to give the correct answer. Concluding the cause difficulties of students’ vocabulary in learning English are the first students difficulties in pronouncing the words. Grammatical form be the second cause because the written form is different from the spoken form in english. The last, students does not give their attention to study english more, knowing a words much more, and limitations their time to sources of information about new words vocabulary. The last, forgot the words easily. Keywords : Analysis Students’ Vocabulary, Difficulties, Cause